Pengaruh Belanja Daerah dan Pertumbuhan Ekonomi Daerah Terhadap Kemandirian Keuangan Daerah di Provinsi Jambi - -, Suherman; Herlin, Faradilla; Neldawaty, Rika; Aldi Yanda, Rahmad; Suherman (Islamic Economics Department, Faculty of Islamic Economics and Business, UIN SULTHAN THAHA SAIFUDDIN JAMBI, 2023)
This research is entitled